The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1516-14392007000400010
|View full text |Cite
|
Sign up to set email alerts
|

WC-CoCr coatings sprayed by high velocity oxygen-fuel (HVOF) flame on AA7050 aluminum alloy: electrochemical behavior in 3.5% NaCl solution

Abstract: In the present work, the electrochemical behavior of WC-CoCr coatings with 10 (W10), 15 (W15) and 20 (W20) torch passes sprayed by High Velocity Oxygen-Fuel (HVOF) flame on AA7050 aluminum alloy substrate, evaluated in 3.5% NaCl solution, were compared using open-circuit potential (E OC) measurements, electrochemical impedance spectroscopy (EIS) and polarization curves. The coating surfaces and their cross sections were characterized by X ray diffraction and the Rockwell-C hardness test, and also by optical (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…6). This behavior has been seen in several coating systems in which the coating is very dense and can form a passive layer such as HVOF-sprayed stainless steel coating [17], hydrothermal deposited TiO 2 [18] and HVOF-sprayed WC-CoCr coating [19] in 3.5% NaCl solution.…”
Section: Electrochemical Impedance Spectroscopy Of the Coatingsmentioning
confidence: 74%
“…6). This behavior has been seen in several coating systems in which the coating is very dense and can form a passive layer such as HVOF-sprayed stainless steel coating [17], hydrothermal deposited TiO 2 [18] and HVOF-sprayed WC-CoCr coating [19] in 3.5% NaCl solution.…”
Section: Electrochemical Impedance Spectroscopy Of the Coatingsmentioning
confidence: 74%
“…Understanding the influence of carbon loss on the corrosion resistance for cases such as the one observed for DGS coating could be enhanced by further research. It has also been reported (Ref 13,14) that carbide particles can cause galvanic corrosion in the matrix, or crevice corrosion can take place at the carbide-matrix interface, especially when the metal matrix has passivation capabilities.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have indicated that carbide size and distribution influences the mechanical properties of these coatings (Ref 7 -10). However, for service in corrosive environment, either Cr 3 C 2 -based compositions such as Cr 3 C 2 -NiCr, or compositions with chromium-alloyed binders such as WC-10Co4Cr and WC-NiCrBSi are the preferred technical solution (Ref [11][12][13][14][15]. In general, understanding the corrosion behavior of HVOF-sprayed WC-Co coatings is not trivial because of their complex microstructures comprising formation of new and nonequilibrium phases, as well as partial carbide dissolution into the metal matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the research efforts on HVOF spraying of cermets on Al-alloys deal with the fatigue (mainly) [40][41][42][43][44][45][46] and wear performance [43,[47][48][49][50] of the coated alloys and they refer to microcrystalline coatings. The works dealing with the corrosion behaviour of HVOF cermet coatings on Alalloys are also relatively few [12,47,49,[51][52][53][54][55], whilst they also refer to microcrystalline coatings. These works have produced quite encouraging results regarding the application potential of hardmetal coatings on Al-alloys.…”
Section: Introductionmentioning
confidence: 99%